Downside risk similarity and M&As - Chen, Lei; Huang, Allen H.; Wang, Xinlu; Xu, Liang (Contemporary Accounting Research, 2026)
Abstract Downside risks are ubiquitous and can profoundly impact firm operations and valuation. Failure to adequately assess and manage target firms' downside risks hinders acquirers' ability to integrate and manage these businesses. This article introduces a novel measure of firms' downside risk similarity (DRS) based on risk factor descriptions and examines its implications for mergers and acquisitions (M&A) outcomes. We first validate that the measure is distinct from existing similarity measures and that it captures similarity in firms' potential significant downside. Using the new measure, we find that the market reacts more positively to deals in which acquirers and targets share more downside risks. Additional analyses show that this beneficial effect of DRS is driven primarily by risks that are idiosyncratic or firm‐specific, consistent with these risks requiring acquirers' relevant expertise to manage. Last, we document that in deals with more similar downside risks, the acquirers experience fewer risk profile changes and are less likely to suffer from adverse outcomes, such as deal‐specific goodwill impairment, divestitures, and significant profitability declines. Overall, we conclude that DRS plays a significant role in the M&A process.